Locally-Generated Revenue as A Capacity Parameters of New Regional Autonomy Management - Titi Darmi (Magister Administrasi Publik, 2018)
Non-human resources play a role in the implementation of the New Autonomous Region (DOB) one of which is the financial resources of the region. In order for the financial capacity of the region can be managed optimally then the appropriate method is to increase its management capacity. The study was conducted in Seluma District as the autonomy mandate of new autonomous regions. The objective of the research is to analyze the extent of the financial management capacity of Seluma Regency as a DOB provider. The research approach is done by qualitative descriptive method, data source is derived from secondary data in the form of, records of financial condition, documentation, financial report that is Report of Result of Inspection (LHP) from BPK, report of APBD realization and regulations related to financial management implementation. Primary data comes from interviews and FGDs to informants. Data analysis through data collection, data condensation, data presentation and decision making or data verification. The results show that the financial management capacity of Seluma Regency has not been done effectively and efficiently, confirmed by the following conditions: 1) the results of supervision of the implementation of the work program found many cases of TGR; 2) low PAD that only contribute 3% range to APBD; 3) financial management got WDP opinion from BPK during last 3 years.